The Use of FDG PET-CT Imaging for the Assessment of Early Antifungal Treatment Response in Disseminated Fusariosis. (July 2017) - Seban, Romain-David; Bonardel, Gérald; Guernou, Mohamed; Lussato, David; Queneau, Mathieu
Abstract : Abstract: Fusariosis is an opportunistic infection, caused by a filamentous fungus, found on plants and in soil. The treatment of disseminated pattern, seen in immunocompromised patients with severe neutropenia, is difficult because of antifungal therapy resistance. A 12-year-old girl, who was diagnosed with B-cell acute lymphoblastic leukemia, developed multiple widespread skin papules and subcutaneous nodules, at day 20 of consolidation therapy. Histological examination with cultures of skin tissue revealed Fusarium species. Treatment was started with intravenous liposomal amphotericin B and voriconazole. To assess treatment response, FDG PET/CT performed at baseline, at 2 and 4 months, showed a partial response.